PENGARUH KEMANDIRIAN BELAJAR DAN REGULASI DIRI TERHADAP HASIL BELAJAR MATEMATIKA MELALUI MOTIVASI BERPRESTASI PADA SISWA KELAS X SMA NEGERI DI KOTA AMBON - Gamar Assagaf (MATEMATIKA DAN PEMBELAJARAN, 2016)
The main problem considered in this study, the quality of education is not determined by a single factor that student learning outcomes are a reflection of the effort to learn, the better the learning effort, the better the results achieved. Good learning outcomes will be achieved if the They can overcome the learning difficulties they experienced, but there are a number of variables that influence each other. The study aimed at discovering the description and the influence of independent learning and self regulation toward learning result of mathematics subject through achievement motivation of grade X at SMAN in Ambon. The study an ex-post facto research with causality. The subject of the study were students of grade X at SMAN in Ambon of academic year 2013/2014 selected by employing proporsional stratified cluster random sampling technique. The instrument used were (1) scale of independent learning, (2) scale of self regulation, (3) scale of achievement motivation, and (4) test of learning result of mathematics of grade X. data were analyzed by employing statistics descriptive and path analysis. The result of the study revealed that (1) most students of grade X at SMAN in Ambon have independent learning with high category, self regulation with high category, and learning result in fair category; (2) independent learning gave positive influence toward learning result of mathematics subject direct ad indirectly through achievement motivation; (3) self regulation gave positive influence towards learning result of mathematics subject direct ad indirectly through achievement motivation. Key Words: learning result, independent learning, self regulation, and achievement motivation.